A new hypercarnivorous hyaenodont from the Eocene of South China - Averianov, Alexander; Obraztsova, Ekaterina; Danilov, Igor; Jin, Jian-Hua (Frontiers in Ecology and Evolution, 2023)
A new hyaenodont Maocyon peregrinus, gen. et sp. nov., is described based on a partial skull and associated mandibles from the upper Eocene Youganwo Formation at Maoming locality in Guangdong Province, China. It shows certain similarities with the Hyainailouroidea in the skull structure, including anteroposteriorly extended jugal/squamosal suture, presence of a preglenoid crest, a lateral expansion of the squamosal posterior to the zygomatic arch, a transversally expanded mastoid process, a nuchal crest that does not extend laterally to mastoid process, and large occipital condyles. The phylogenetic analysis clusters the new taxon with Orienspterodon from the late middle Eocene of China and Myanmar and places this clade as the sister taxon to the Hyainailouroidea. This advocates for the origin of the latter clade from an Asian ancestor.